Coronary drug‐eluting stents: From design optimization to newer strategies. Issue 5 (1st July 2013) - Sun, Daming; Zheng, Yiming; Yin, Tieying; Tang, Chaojun; Yu, Qingsong; Wang, Guixue
Abstract Compared with early bare‐metal stents, drug‐eluting stents (DESs) are more effective in treating coronary artery diseases, especially in inhibiting restenosis. However, in‐stent restenosis still clinically occurs at a non‐negligible rate. More importantly, delayed endothelialization, inflammation, and hypersensitivity trigger subacute or late adverse events, particularly stent thrombosis, and thereby raise more concerns over the long‐term safety of DESs. These problems are mostly associated with the permanent polymeric materials, non‐optimal therapeutic drugs, and/or metallic stent platforms used in current DES design. It is critically important to further improve and optimize DES design and apply newer strategies for developing next generation DES. These new generation DESs should maintain their clinical efficacy and meanwhile eliminate the long‐term safety concerns. In this review article, the current information on the optimization of DES design was critically reviewed based on DES's basic components, namely, stent platform, restenotic drug, and polymer coating. The available strategies for designing next‐generation DESs were also summarized, ranging from degradable polymer DESs, to polymer‐free DESs, to fully biodegradable DESs. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 1625–1640, 2014.